The Influence Of Work Ethics, Work Discipline, And Work Motivation On Work Productivity Of Private Office In North Sumatra - setiawan, nashrudin; Teguh Waluyo; Rindi Andhika (Journal Of Management Analytical and Solution (JoMAS), 2023)
This research was conducted to find out how The Effect Of Work Ethos, Work Discipline, And Work Motivation On Work Productivity Of Private Offices In North Sumatra The number of samples was 73 respondents. This research was conducted in 2022. This research used quantitative data processed with SPSS 24.0 with multiple linear regression models. The results showed that work ethic, work discipline, and work motivation both partially and simultaneously had a positive and significant effect on the work productivity of the employees of the Regional Office of the Ministry of Religion of North Sumatra. Work discipline was the most dominant variable affecting work productivity with tcount of 4.141. In addition, 91.8% of work productivity could be explained and obtained from work ethic, work discipline, and work motivation, while the rest was due to other factors. Work productivity had a very strong relationship to work ethic, work discipline, and work motivation.